Una rilettura della vicenda nietzscheana - Tronti, Mario (B@belonline, 2021)
In Massimo De Angelis’ book Is God still useful? we go through the work of Nietzsche going through his own existence. And the subtitle sounds clear: Nietzsche’s way beyond nichilism. The whole path of a thought is reconstructed, chapter by chapter, better movement by movement. De Angelis follows the course, even dramatic of a life. Not an easy job, infact. And the speech is scanned by pointing out the different passages with the movements of musical language.